An enhanced strategy based on the pyrolysis of bean dregs for efficient selective recovery of lithium from spent lithium-ion batteries. Issue 24 (1st December 2022) - Lin, Tianning; Wang, Yue; Jin, Shan; Mu, Deying; Zhang, Jian; Liang, Jianquan; Dai, Changsong
Abstract : Bean dregs were exploited as a green reducing agent, and adopted an enhanced recycling process combining biomass reduction roasting and carbonated water leaching to efficiently and selectively recover Li from the spent LIBs. Abstract : With the vigorous development of the lithium-ion battery (LIB) industry, the scarcity and non-renewability of lithium resources mean that the efficient selective recovery of Li from the spent LIBs turns progressively essential. Herein, by utilizing bean dregs (BDs) as a green reducing agent, an enhanced recycling strategy combining biomass reduction roasting and carbonated water leaching was explored. During the roasting process, the pyrolysis of BDs promoted the decomposition of the cathode material and converted it into Ni, Co, MnO, and Li2 CO3 . According to the thermodynamic analysis and the physical characterization of roasted products, a lattice collapse model was exploited to illuminate the thermochemical reaction mechanisms under the synergistic reduction effect of gases and biochar. Moreover, the parameters of the carbonated water leaching process were optimized by the response surface method (RSM) and the central composite design (CCD), and the leaching rate of Li was further enhanced. Economic assessment results indicate that this recycling strategy enhances the total profits by reducing energy and reagent consumption and increasing the recovery efficiency of Li. Overall, based on the pyrolysis of BDs, the enhanced strategy provides new perspectives and expectations for the future spent LIB recycling industry.